CUSTOMER SATISFACTION IN TERMS OF PRODUCT QUALITY, SERVICE, PROMOTION AND MARKETER COMPETENCE ON PT. TIGA SERANGKAI PUSTAKA MANDIRI SURAKARTA BRANCH - Sujita Sujita; Istiatin Istiatin; Sudarwati Sudarwati; Dewi Hermawati Wahyuningsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine customer satisfaction in terms of product quality, service quality, sales promotion, marketer competence. The research was conducted at PT. Tiga Serangkai Pustaka Mandiri of Surakarta Branch Independent with a sample of 100 customers by providing a questionnaire through google.form for the period 5 May – 11 June 2022. Data analysis techniques use multiple linear regression with the help of the IBM SPSS 21 computer program. The results of the study found that statistically customer satisfaction is predicted to be influenced by factors of product quality, service quality, sales promotion and marketer competence. The predictive range with adjusted R Square obtained customer satisfaction influenced by product quality, service quality, sales promotion and competence reached 71.6%. The value of the regression coefficient of the marketer's competency variable is the largest value among other variables, this indicates that the competence of marketers has a very large influence on customer satisfaction at PT. Tiga Serangkai Pustaka Mandiri of Surakarta Branch. Keywords : customer satisfaction , product quality, service quality, sales promotion, marketer competence